From Traditional Market to Urban Social Space: The Historical Transformation of Pasar Bawah in Bukittinggi from the Precolonial Era to the Present - Nova Amelia Putri; Aisiah Aisiah; Ahmad Nurhuda (UIN Imam Bonjol Padang, 2026)
This study aims to analyze the historical transformation of Pasar Bawah in Bukittinggi from a social history perspective. The study focuses on the transformation of Pasar Bawah from a traditional market that served as a community trading space to an urban social space associated to commercial activities, tourism, community mobility, and social interaction. Pasar Bawah was selected as the research subject because of its strategic location in the center of Bukittinggi and its proximity to Jam Gadang, Pasar Ateh, shopping districts, pedestrian paths, and various centers of community activity. These conditions have allowed Pasar Bawah to function not only as a site of economic transactions but also as a space that reflects the dynamics of urban development and community life. This study employs a historical method with a descriptive qualitative approach. Data were collected through field observations, in-depth interviews, documentation, government records, historical documents, and literature reviews. Data analysis was conducted through the stages of heuristics, source criticism, interpretation, historiography, and thematic analysis. The findings indicate that Pasar Bawah has deep historical roots closely connected to the development of Bukittinggi as a trading city. As the city has evolved, the function of Pasar Bawah has shifted from a traditional marketplace to a social space that connects the community’s economic activities, population mobility, and tourism. Interactions among vendors, shoppers, tourists, and the surrounding community foster social relationships based on communication, trust, cooperation, and daily economic activities. This study demonstrates that Pasar Bawah not only holds economic value but also serves as a space of social history that reflects the interconnections between trade, urban development, tourism, and the historical identity of the city of Bukittinggi